Multi-innovation stochastic gradient method for harmonic modelling of power signals - Zhou, Lincheng; Li, Xiangli; Xu, Huigang; Zhu, Peiyi (IET signal processing, 2016)
The harmonic parameter identification and modelling problem for power signals are studied. In order to model power signals, the multi-innovation stochastic gradient (MI-SG) is derived based on the multi-innovation identification theory. The proposed MI-SG algorithm repeatedly uses past innovations by expanding the scalar innovation to the innovation vector and can obtain more accurate parameter estimates than the stochastic gradient algorithm. Finally, the simulation results indicate that the proposed algorithm is effective and has a close estimation accuracy compared with the fast Fourier transform analysis.